2016
DOI: 10.1007/s12230-016-9515-7
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Fertilizer Rate for Fresh Market Potato Cultivars Grown in Tropical Soil with Low Phosphorus Availability

Abstract: Knowledge on phosphorus (P) response of main potato cultivars is essential to rational fertilization management and maximize yield, mainly in tropical soils that usually have low P availability. An experiment was conducted to evaluate the effect of P fertilization rates (0, 125, 250, 500, and 1000 kg P 2 O 5 ha −1) on leaf nutrient concentrations, tuber yield and size distribution, as well as applied P-use efficiency (APUE) in the potato cultivars Agata and Mondial. The results indicated that it is not necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…The increase in fresh tuber yield and tuber DM yield up to the rates of 500, 250, and 125 kg ha -1 P 2 O 5 in soils with low, medium, and high initial P availability, respectively, indicates that at high soil P availability, there is no need to apply high P rates to potato (Figures 5a and 5b). Other studies have indicated no increase and/or only small increases in potato tuber yield in response to the application of high P rates in soils with high initial P availability (Rykbost et al, 1993;Hochmuth et al, 2002;Rosen and Bierman, 2008;Luz et al, 2013;Rosen et al, 2014;Fernandes and Soratto, 2016). However, Brazilian producers still commonly apply rates higher than 600 kg ha -1 P 2 O 5 in potato-growing areas (Sangoi and Kruse, 1994;Fernandes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in fresh tuber yield and tuber DM yield up to the rates of 500, 250, and 125 kg ha -1 P 2 O 5 in soils with low, medium, and high initial P availability, respectively, indicates that at high soil P availability, there is no need to apply high P rates to potato (Figures 5a and 5b). Other studies have indicated no increase and/or only small increases in potato tuber yield in response to the application of high P rates in soils with high initial P availability (Rykbost et al, 1993;Hochmuth et al, 2002;Rosen and Bierman, 2008;Luz et al, 2013;Rosen et al, 2014;Fernandes and Soratto, 2016). However, Brazilian producers still commonly apply rates higher than 600 kg ha -1 P 2 O 5 in potato-growing areas (Sangoi and Kruse, 1994;Fernandes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The largest increases in potato tuber yield have come from P applications, especially in P-deficient soils (Fontes et al, 1997;Alvarez-Sánchez et al, 1999;Rosen and Bierman, 2008;Soratto et al, 2015;Fernandes and Soratto, 2016), although K, N, and Ca are taken up in greater amounts by potato plants (Fernandes et al, 2011). Since costs are high in establishing the potato crop, many farmers prefer to ensure high yields through possible over application of fertilizers than to adhere to the recommended levels for fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…This cultivar has low P-use efficiency (Soratto et al, 2015) and can respond to high P fertilizer rates in the planting furrows, especially in soils with low and medium P availability (Fernandes & Soratto, 2016). N and K are the nutrients taken up in greater amounts by 'Atlantic' potato plants, but this cultivar uptakes maximum only 26% N and 35% K of total required until 40 days after planting (DAP) , which is inconsistent with 4-14-8 rates traditionally applied in the planting furrows.…”
Section: Resumo Produtividade De Tubérculos E Resultado Econômico Da mentioning
confidence: 99%
“…Potato (Solanum tuberosum L.) cultivation is highly demanding for nutrients available in the soil because of its short cycle, high growth rate, and high yield per unit of area (Fernandes et al, 2011;Fleisher et al, 2013;Fernandes & Soratto, 2016a). Phosphorus (P) ranks first among the macronutrients whose deficiencies are most limiting for potato yield in tropical soils (Luz et al, 2013;Fernandes & Soratto, 2016a, 2016b. This occurs because the recovery of fertilizer P by plants is usually very low due to the high capacity of soils to adsorb/bond P to soil constituents, especially in acid clayey soils (Falcão & Silva, 2004;Novais et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In soils with low P availability, potato shows reduced stem length, leaf size and number, and leaf area, compromising the plant dry matter (DM) production (Fleisher et al, 2013;Fernandes & Soratto, 2016b). The number, size, and yield of tubers are also significantly reduced (Fleisher et al, 2013;Luz et al, 2013;Fernandes & Soratto, 2016a, 2016b. Therefore, high rates of P fertilizer have been applied in potato cultivation, and the use efficiency of applied P is usually low (Luz et al, 2013;Fernandes & Soratto, 2016a).…”
Section: Introductionmentioning
confidence: 99%